Otimização da produção de ésteres etílicos e metílicos a partir do óleo de buriti (Mauritia flexuosa) e suas caraterizações - Silva, Mirian Santos da (2019)
Buriti is a palm tree of great importance for the environment and for several families that survive on the income generated from the products made with their fruits or leaves. Buriti oil is one such product, it is used in many ways by families. Increasing the possibilities of using this oil is important in order to further open the options for selling this product. From this context, the syntheses of methyl and ethyl esters from buriti oil were performed, and their respective characterizations. A central composite design was proposed to optimize the production of biodiesels, evaluating the alcohol: oil ratio, catalyst percentage and reaction time, at two levels each. All these variables were analyzed totaling seventeen reactions to be subjected to factorial design. The maximum conversion of crude oil to methyl esters was achieved at a molar ratio of 1:10 (oil / methanol) at 120 min reaction time using 3% catalyst, reaching 98.82% yield. The characterization results (kinematic viscosity, relative density, ester content and acidity index) of the methyl and ethyl esters were satisfactory compared to the standards required by the ANP for the biodiesels.